Advances in the Prevention and Treatment of High-Altitude Illnesses - Kowalik, Filip; Deczkowska, Maria; Stasiak, Olga; Wielogórska, Aleksandra (Journal of Education, Health and Sport, 2026)
Introduction and purpose High-altitude environments (>1500 m) expose climbers to reduced atmospheric pressure and hypoxia. These conditions increase the risk of acute mountain sickness, high-altitude cerebral edema, and high-altitude pulmonary edema. This review aims to summarize current knowledge of high-altitude illnesses (HAI), their prevention and treatment, with particular emphasis on recent advances in this field. A brief description of the state of knowledge Prophylaxis of HAI is based on proper acclimatization and a suitable ascent rate. Acetazolamide is among the most commonly used agents for pharmacologic prophylaxis. Treatment in severe cases requires prompt descent, oxygen therapy, dexamethasone, or portable hyperbaric chambers. There are numerous novel strategies used for reducing the risk of HAI. Emerging evidence suggests that probiotics may facilitate acclimatization. Pre-acclimatization and hypoxic training at sea level enable preparation for high-altitude exposure. Wearable sensors and closed-loop systems may provide more precise risk assessment; however, their effectiveness in mountainous conditions remains to be improved. Advanced prediction models, in turn, additionally improve the identification of people from risk groups and facilitate personalized prophylaxis. Summary (conclusions) HAI remain an important challenge in hypoxic, mountainous conditions. Apart from the currently well-established methods, novel strategies, such as probiotics, hypoxic training, and advanced monitoring technologies, may facilitate prophylaxis and individual risk assessment, thus improving the security of high-altitude expeditions.